Effects of crisis response tone and spokesperson's gender on employer attractiveness. (April 2021) - Kapuściński, Grzegorz; Zhang, Nathan; Zeng, Liting; Cao, Aihua
Highlights: The study determines the effect of apology on hospitality organisations' employer attractiveness. The study tests theories of crisis communication in a social media employer branding context of hospitality. The study used a 2 (apology tone) by 2 (spokesperson gender) between-subjects experimental design. The findings demonstrate a moderated mediation effect. Abstract: Timely apologies to key publics on social media are becoming an important aspect of crisis recovery but little is known of how the spokesperson's characteristics and the tone of apology may influence the outcome. Recognising the importance of the need to attract quality workforce, this study examines the impact of social media response to a preventable crisis on organisational attractiveness. Specifically, a 2 (message tone: corporate/formal vs. human/informal) x 2 (spokesperson's gender: male vs. female) between-subjects factorial design was used to test the effectiveness of an apology. The results suggest a significant moderated mediation effect. We find that account acceptance mediates the relationship between message tone and organisational attractiveness, and this effect is conditional on gender of the spokesperson. The results are relevant to crisis managers and brand managers that seek to attract and retain talents.